Beberapa Hasil Penelitian yang Mendukung Manfaat Tumbuhan Jambu Biji (Psidium guajava L.) - Hargono, Djoko (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
Generally guajava is known as a plant, which all of its parts are used as adstringent. But research results shown that this plant has some efficacies, for instance us analgesic, antibacterial, antidiabetic, antispasmodic, anti inflamation etc. Recently the people also use the ripe guajava fruit juice, especially the red one, as a remedy for of dengue infection, which its scientific background is not known yet. Therefore many research activities should be done in order to know what efficacies are shown by any part of guajava plant.